Property of electrospinning silk fibroin nanofibers prepared by different dissolved methods - Wu Huiying; Zhou Yan; Yao Ping; Ding Maomao (MATEC Web of Conferences, 2016)
In the present study, silk was dissolved in CaCl2-formic acid and CaCl2-C2H5OH-H2O to obtain silk fibroin solution. The dissolve process, morphology, structure and mechanical properties of nanofibers prepared by electrospinning were studied. It showed that nanofibril structures were exhibited in the silk fibroin solution in CaCl2-formic acid compared with traditional method dissolving in CaCl2-C2H5OH-H2O solution, and the viscosity of the solution was much higher. The average diameter of nanofibers prepared by CaCl2-formic acid dissolution method was 375±26nm, and it showed well drawability, after stretching to 1 times, its breaking strength and elongation at break reaching 18.6±3.8MPa and 14.0±2.5%, respectively, was improved obviously relative to nanofibers prepared by CaCl2-C2H5OH-H2O dissolution method. It demonstrated that the good mechanical property of fibers was contributed to the fibrillar structures in the solution.